Monosodium glutamate induced histological change in the Zona Fasiculata of rats' adrenal and the possible amelioration effect of vitamin C supplementation - Abdo, Fadia K; Hassan, Zeinab A; Mohamed, Dalia A; Mousa, Hanaa S (Journal of Medicine and Health Sciences Research, 2018)
Monosodium glutamate in gesting (MSG) is steadily increasing worldwide as a flavour enhancer and food additive. On the other hand, vitamins C has antioxidant properties and can play an important role in preventing or improving many diseases. So, the aim of the present study is to study the impact of MSG administration on the histological structure of the zonafasciculata (ZF) of adult albino rat adrenal cortex and to clarify the possible amelioration effect of vitamin C cosupplementation. Thirty adult male albino rats were divided equally into three groups: group I; negative and positive (received100mg/kg vitamin C) control subgroups. MSG-treated group were administered 2 mg/g body weight MSG via gastric tube andascorbic acid supplemented group were given the same dose of MSG, followed by vitamin C at a dose similar to the positive control group. Tissue sections were obtained and proceeded for light and electron microscope examination. Plasma ACTH and cortisone were estimated. Morphometric and statistical analysis of the results were performed. Plasma ACTH and corticosterone levels in the MSG-treated group were significantly increased comparing to control and MSGtreated group receiving vitamin C. Histologically, in the MSG-treated group, ZF contained highly vacuolated cells and congested blood vessels. The reticular fibres were increased in MSG-treated group decreased in ascorbic acid supplemented group. Ultrastructurally, ZF contained cells with shrunken nuclei and numerous macrophages containing many lysosomes. On the other hand, the cellular architecture of ascorbic acid supplemented group was less affected and congested blood sinusoids were still detected. The reticular fibres were decreased in ascorbic acid supplemented group. Oral administration of MSG caused histological and functional degenerative changes in the ZF of adrenalin adult male albino rat which was ameliorated by supplementation of vitamin C. So, it is recommended to minimize consumption of foodstuffs containing MSG and to eat foods rich in vitamin C after performing more researchers to be sure of these effects on humans.MSG